High Altitude Wetlands as Ramsar Sites in Nepal: Status after Declaration - Karki, Jhamak B (Journal of Wetlands Ecology, 2008)
No abstract.DOI: 10.3126/jowe.v1i1.1566 Journal of Wetlands Ecology Vol.1(1/2) 2008, p.13